The role of IL-17, IL-23 and IL-31, IL-33 in allergic skin diseases. Issue 4 (August 2020) - Topal, Fatih A.; Zuberbier, Torsten; Makris, Michael P.; Hofmann, Maja
Abstract : Purpose of review: Allergic skin diseases such as urticaria, atopic dermatitis and allergic contact dermatitis are among the most common skin diseases with severe socioeconomic consequences. The pathogenesis of allergic skin diseases is complex. This review provides an overview of cytocines IL-17, IL-23, IL-31 and IL-33. Recent findings: Current research results show a variety of immunological processes in the pathogenesis of the allergic skin diseases, including the role of cytokines. In addition to the Th1 and Th2 immune response, the immune response via Th17 is becoming increasingly important in allergic skin diseases but also the cytokines IL-23, IL-31 and IL-33 have been discussed in the literature recently. Different cytokines promote in a kind of orchestra the different symptoms seen in the different allergic skin diseases, including pruritus, dermatitis, mast cell mediator release and inflammation. Summary: We are still in the early stages of understanding pathophysiology of allergic skin diseases and the role of various cytokines in the immune system. With the development of targeted antibodies against the proinflammatory cytokines, the variety of normal therapeutic options can be expected to evolve.